2015
DOI: 10.1038/srep12623
|View full text |Cite
|
Sign up to set email alerts
|

Colokinetic effect of noradrenaline in the spinal defecation center: implication for motility disorders

Abstract: Chronic abdominal pain in irritable bowel syndrome (IBS) usually appears in combination with disturbed bowel habits, but the etiological relationship between these symptoms remains unclear. Noradrenaline is a major neurotransmitter controlling pain sensation in the spinal cord. To test the hypothesis that the descending noradrenergic pathway from the brain stem moderates gut motility, we examined effects of intrathecal application of noradrenaline to the spinal defecation center on colorectal motility. Colorec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 27 publications
4
32
0
Order By: Relevance
“…We previously demonstrated that intrathecal administration of NA and DA caused propulsive contractions of the colorectum via activation of the lumbosacral defecation center. These findings allow us to propose a novel hypothesis that descending pain inhibitory pathways modulate not only pain but also the defecation reflex in the lumbosacral spinal cord . This study showing that 5‐HT injected into the lumbosacral spinal cord activates colorectal motility confirms our hypothesis, because 5‐HT is known to be a neurotransmitter of the descending pain inhibitory pathways, the origin of which is the rostral ventromedial medulla including the raphe magnus .…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…We previously demonstrated that intrathecal administration of NA and DA caused propulsive contractions of the colorectum via activation of the lumbosacral defecation center. These findings allow us to propose a novel hypothesis that descending pain inhibitory pathways modulate not only pain but also the defecation reflex in the lumbosacral spinal cord . This study showing that 5‐HT injected into the lumbosacral spinal cord activates colorectal motility confirms our hypothesis, because 5‐HT is known to be a neurotransmitter of the descending pain inhibitory pathways, the origin of which is the rostral ventromedial medulla including the raphe magnus .…”
Section: Discussionsupporting
confidence: 76%
“…In previous studies, we showed that NA and DA have colokinetic effects in the lumbosacral defecation center. 14,15 Since 5-HT activates sacral parasympathetic preganglionic neurons, in a similar way to the actions of NA and DA, it was of interest to examine the interaction be- Figure 5D). It should be noted that the mixture of NA and DA did not enhance colorectal motility in the absence of preceding 5-HT (data not shown).…”
Section: Interaction Between the Actions Of 5-ht Na And Damentioning
confidence: 99%
See 2 more Smart Citations
“…The reverse potential of K + in this experiment was around −90 mV, which the pontine micturition center, and administration of NA initiates the micturition reflex in some bladder conditions (28). Also, α1 receptor-mediated facilitations of colonic mortalities in the spinal cord were reported in defecation systems (22,23). Our findings showing excitation through α1 receptor of labeled-PGNs and enhancement of sEPSC may explain the mechanisms of those reports.…”
Section: Direct Effects Of Na In Dii-labeled Spn Neuronssupporting
confidence: 62%